Anthocyanins standards (cyanidin-3-O-glucoside and cyanidin-3-O-rutinoside) isolation from freeze-dried açaí (Euterpe oleraceae Mart.) by HPLC Isolamento de padrões de antocianinas (cianidina-3-O-glucosídeo e cianidina -3-O-rutinosídeo) de açaí liofilizado (Euterpe oleraceae Mart.) por CLAE - Ana Cristina Miranda Senna Gouvêa (Food Science and Technology, 2012)
Availability of analytical standards is a critical aspect in developing methods for quantitative analysis of anthocyanins. The anthocyanins cyanidin-3-O-glucoside and cyanidin-3-O-rutinoside were isolated from samples of freeze-dried açaí (Euterpe oleraceae Mart.), which is a round and purple well-known palm fruit in Brazil, and then used as standards. The isolation of the anthocyanins was performed by High Performance Liquid Chromatography (HPLC), using an adapted six-channel selection valve. The identification of anthocyanin pigments in açaí was based on mass spectrometric data for molecular ions and MS-MS product ions and on previous published data. After the collection procedure, standards with a high purity grade were obtained and an external standard curve of each anthocyanin was plotted. Disponibilidade de padrões analíticos é um aspecto crítico no desenvolvimento de métodos de análises quantitativas de antocianinas. Para a obtenção dos padrões isolados de antocianinas cianidina-3-O-glicosídeo e cianidina-3-O-rutinosídeo foram utilizadas amostras liofilizadas de açaí (Euterpe oleraceae Mart.), que é um conhecido fruto de palmeiras no Brasil de forma arredondada e roxo. O isolamento das antocianinas foi realizado por Cromatografia Líquida de Alta Eficiência (CLAE), utilizando uma válvula seletora de seis canais. A identificação de antocianinas no açaí foi baseada em dados publicados na literatura e por espectrometria de massas. Após a coleta, padrões com um alto grau de pureza foram obtidos e uma curva para padronização externa de cada antocianina foi feita.